PENGARUH SERTIFIKASI TERHADAP KOMPETENSI PROFESIONAL GURU SEKOLAH MENENGAH ATAS DI ACEH JAYA - Chairan M Nur (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Certification is the process of giving educator certificates to teachers as recognition as professionals. Sometimes, the teacher in delivering material is difficult to accept or understand by student learning. This study aims to obtain information about the effect of certification on the professional competence of high school teachers in Aceh Jaya. The results showed a significant effect, it can be proven by the results of a questionnaire analysis of the variable professional competence of teachers and teacher certification. In the teacher professional competency variable, both planning indicators, implementation indicators, and assessment indicators are all very high criteria. Whereas the teacher certification variable shows that academic qualifications, teaching experience, planning and implementation of learning, assessments from superiors and supervisors, academic achievements, participation in scientific forums, the experience of being an organization administrator in the educational and social fields are all in the very high category, except education and training in the low category and professional development work and awards that are relevant to the education sector in the sufficient category.